PELATIHAN AKSES DAN STRATEGI PEMASARAN UMKM di ERA DIGITAL MENUJU DIGITAL MATURITY - Ari Agung Nugroho; Wenni Anggita; Nanang Wahyudin; Sigit Nugroho (Jurnal Abdi Insani, 2023)
According to the 2020 Asia Pacific SMB Digital Maturity Study which was made based on the results of a survey of SMEs from all regions in the Asia Pacific by the International Data Corporation (IDC) according to the Cisco Commission, there are 4 (four) MSME maturity levels. The four levels are digital indifferent, digital observer, digital challenger and digital native. According to this study, the majority of MSMEs in Indonesia are still in the first stage or more precisely, ranked 13th in Asia Pacific. However, as many as 82 percent of MSMEs in Indonesia have the desire to transform digitally so they can bring new products and services to the market. Therefore, efforts are needed to make MSMEs more digitally literate, one of which is providing knowledge related to digital marketing through effective use of social media. The implementation of this service activity is by providing training related to the use of social media as a means of marketing products more effectively in the current era of digitalization. MSME players are given tips and tricks on how to create content, how to create words that attract buyers so that the product is better known. The output of this activity is that MSMEs are motivated to make more use of social media as a marketing tool and MSMEs have business accounts on their social media that will be used for promotions